(untitled) (BIRDEM Medical Journal, 2024)
Background: Hemodialysis has become an increasingly safe and well tolerated therapy for patients with endstage renal disease (ESRD). The aims of this study were to evaluate clinical and laboratory profile of the ESRD patients undergoing maintenance hemodialysis. Methods: This cross-sectional study was carried out in the Department of Nephrology and Dialysis of BIRDEM General Hospital, Dhaka, Bangladesh from November to December, 2015. After taking informed consent from the patients, clinical data were taken from history and physical examination findings and laboratory data were collected from record books of the patients. Results: Total patients were 107, male were 78 and female were 29. The mean age was 57.3 ± 11.4 years. Mean duration of chronic kidney disease (CKD) was 5.7 ± 4.2 years. Diabetic nephropathy was the most common (43%) cause of CKD. Maximum duration of dialysis was 6.5 years with mean of 1.73 ± 1.25 years. Over twothirds (68.2%) of the patients were on thrice-weekly dialysis and rest (31.2 %) were on twice-weekly dialysis. In majority (91.6%) of the patients dialysis was initiated through temporary catheter. Eighty five percent of the patients were on anti-hypertensive medications. The mean pre-dialysis systolic and diastolic blood pressures were 151 and 85 mm Hg respectively and the mean post-dialysis systolic and diastolic blood pressures were 146 and 80 mm Hg respectively. Mean hemoglobin was 9.01 gm/dl, mean ferritin was 947.6 ìg/dL. Sixty five percent patients were on treatment for anemia, with either erythropoiesis-stimulating agent (ESA) or iron or both. Eighty five percent patients had been vaccinated against Hepatitis B virus. The mean serum calcium, phosphate and parathyroid hormone was 8.87 mg/dL, 5.69 mg/dL and 245.2 pg/mL respectively. About one-third (31.2%) patients had history of hospitalization in last six months and 23% patients had plan for renal transplantation. Conclusion: Diabetic nephropathy was most common cause of ESRD. A temporary dialysis catheter was the most common initial vascular access. Near two-thirds patients were on thrice weekly dialysis. Our patients’ blood pressures were controlled with medication but were mildly anemic and had mild mineral abnormality. BIRDEM Med J 2024; 14(2): 70-74